SEDIMENTATION RATE BASED ON OCEANOGAPHIC PARAMETERS REVIEWS IN THE ESTUARY OF KAPUAS, CENTRAL KALIMANTAN - Delyuzar Ilahude (Marine Geological Institute of Indonesia, 2011)
Secara geografis daerah penelitian terletak di muara Sungai Kapuas Kalimantan Tengah. Kawasan pantai ini sangat terbuka dipengaruhi oleh aksi gelombang dari arah tenggara, selatan, baratdaya dan barat. Di pesisir pantai muara Sungai Kapuas terdapat arus sejajar pantai yang bergerak masuk ke arah muara. Pergerakan arus sejajar pantai tersebut memasok sedimen dari arah tenggara dan barat ke muara. Sedimen tersebut cenderung diendapkan di sisi barat dari muara Kapuas. Hal ini menjadi kendala alur pelayaran di muara Sungai Kapuas. Kata kunci : arus sejajar pantai, muara, Kapuas Geographically, the study area is located on the coast of Kapuas River mouth, Central Kalimantan. This open beach area is affected by wave action from southeast, south, southwest and west direction. The longshore current drifts to the estuary on the coastal zone of the Kapuas River. It gives potential sediment supply from the southeast to the north. The sediment tends to be deposited in the western part estuary of Kapuas.This particular thing evokes the ship navigation in Kapuas estuary. Keywords : longshore current, estuary, Kapuas